The extent of the effect of saudization on the employment of local labor in private hospitals from the point view of the owner of private hospitals - Alshuhri, Abdulaziz Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to reveal the main factors that obstruct the employment of local Saudi workers in private hospitals instead of foreign worker, and to determine the extent of application of the Saudization process in the Saudi private hospital sector, and to clarify the extent of the impact of the following variables: legal systems, expertise and competence, availability of specialities, and wages on the Saudization process from the viewpoint of owners of private hospitals. The descriptive-analytical method was used to achieve the aims of the study, and the questionnaire was the tool of the study, which distributed among (179) workers from the researched hospitals. The research reached a number of results, the most important of them were: there is a high degree of importance for the Saudization axis in appointing employees in hospitals, and there is a high degree of importance for the following axes: wages, the availability of rare medical specialities, the experience of the medical staff, and the skills of using modern technology. Based on the results the researcher proposed a number of suggestions, among them: The necessity of working on establishing a minimum wage, as the low wages have no effects on employing foreign workers instead of local labor, and the need to work on qualifying the Saudi citizens with the rare and the few specializations in the labor market.